Water in diesel emulsion behavior in high-pressure direct injection system - Aziz, A.R.A. (Springer Singapore, 2019)
This chapter describes the approaches used in micro-explosion studies, fundamentals of the micro-explosion processes, and the main factors influencing the micro-explosion behavior. Moreover, this chapter briefly discussed the effect of injection equipment on the dispersed water droplets size and the results related to their micro-explosion behavior. Â© Springer Nature Singapore Pte Ltd. 2020.